Development of Backpacker Guide Application for Android Based Smartphone - Chen, Rui Chee; Murli, Norhanifah (Applied Information Technology And Computer Science, 2021)
Backpacker is someone who take a vacation or travelling with a backpack. Backpacking is a form of low-budget and independent way of travelling. However, most of backpacker applications which found in Google Play Store are lacking some important features and functions such as lack of routing, bookmark and search functions. Therefore, users are required to install more than one backpacker applications to get enough information and this will occupy the storage and memory of their mobile device. Thus, a Backpacker Guide Application is developed by integrating the features and functions from different applications to meet the backpackers’ requirements. To develop a Backpacker Guide Application in Android mobile platform by using Android Studio and test it by alpha and beta testing to the target user are the objectives of this project. Agile model is chosen as project methodology. The focus of Backpacker Guide Application is to provide tourist spot information and route the user from current location to the destination by using the Google map. The information of the tourist spots will be displayed with description, photos and contact details to the user. Based on the beta testing conducted, the acceptance level achieved is 93%, which there is a high percentage of acceptance from the target users.